Reduksi Torium Pada Limbah Cair Pengolahan Monasit Menggunakan Resin Penukar Anion - Hasna, Laili; Amalia, Suci; Marisi, Dany Poltak (EKSPLORIUM, 2020)
The effect of separating rare earths from monazite is wastewater containing the radioactive element thorium which is harmful to the environment and living things. A standard method of separating thorium from wastewater is with anion-exchange resin. This study determines the optimum type of anion-exchange resin, resin weight, and contact time to reduce thorium levels in monazite wastewater. The results showed that the optimum exchange rate that occurred in Amberlite IRA402 resin is 57.7%, at 60 minutes and 1 gram. Meanwhile, the optimum exchange rate for Tulsion A23 resin is 50.7%, at 50 minutes and 1 gram. The statistical test showed that there was no significant difference in the resin type and contact time variation, which showed a considerable value >0.05. At the same time there was a substantial difference in resin mass variation with a significant value <0.05. The Duncan test stated that lighter resin masses (0.25 and 0.5 gram) are suitable for Tulsion A23 and heavier resin masses (0.75 and 1 gram) are ideal for Amberlite IRA402.